Effects of Tiktok Videos on the Values Development and Academic Performance of Grade 8 Students - Cruz, Karen (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of TikTok videos on the values development and academic performance of Grade 8 students. Employing a descriptive research design, the study gathered data on students’ demographic profiles, their perceptions of TikTok’s influence on values, and their academic performance. Findings reveal that most respondents are 13-year-old males, first-born in families of four, with parents generally having a high school level of education. Fathers are mostly employed in the private sector, while mothers are often unemployed, and families typically belong to low- to middle-income households.Results show that students perceive TikTok videos as having a high influence on their values development, particularly in terms of courtesy, followed by creativity, respect, and responsibility. Overall, TikTok is perceived to often influence these values. Statistical analysis indicates no significant differences in perceived effects when grouped according to age, birth order, family size, parents’ educational attainment, occupation, and income. However, a significant difference was found in terms of sex with respect to the value of respect, while no significant differences were observed in courtesy, responsibility, and creativity.In terms of academic performance, most students achieved a Very Satisfactory rating, with an average grade of 86.61, a highest grade of 96, and a lowest grade of 76. Furthermore, there is no significant relationship between the perceived effects of TikTok on values development and students’ academic performance.The study concludes that TikTok may positively influence certain student values without significantly affecting academic performance. It recommends integrating educational TikTok content into classroom instruction, adopting gender-sensitive teaching strategies, strengthening parental monitoring, and implementing values formation programs aligned with students’ digital exposure. Future research may explore other social media platforms and examine long-term effects on academic outcomes..
Keywords: TikTok, values development, academic performance, Grade 8 students, social media influence, descriptive research, educational technology